Performance of M1 Generation of Echinacea purpurea Accession Two Resulting From Gamma (Ray) Irradiation - Ramadhini, Sindy Jihan Nabilah; Purwanto, Edi; Roviqowati, Fitria; Yunus, Ahmad (Universitas Sebelas Maret, 2024)
Echinacea (Echinacea purpurea) is an herbaceous plant used as a medicinal raw material. Efforts required simplicia extract of Echinaceae is by increasing the diversity and content of secondary metabolites of Echinaceae through gamma ray irradiation. This study was conducted to determine the morphological characteristics as well as the diversity of growth and results of Echinaceae accession two from the results of gamma ray irradiation. The research was carried out by the Tawangmangu Center for Research and Development of Medicinal Plants and Traditional Medicine and in the Experimental Land of the Faculty of Agriculture, Universitas Sebelas Maret Surakarta, Jumantono Subdistrict, Karanganyar Regency in August 2022-February 2023 with a single plant method and without replication. Data analysis was carried out descriptively and boxplot analysis to see the distribution of data and outlier values. The results showed that the dose of gamma ray irradiation gave rise to new variations in the observed character. Irradiation dose increases diversity in plant growth character and yield. A dose of 40 Gy produced amendment extract yield of 12.32%. A dose of 20 Gy produced total flavonoid level of 0.048%.